ANALISIS FAKTOR INTERN YANG MEMPENGARUHI HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS MAN 1 PONTIANAK - Selpia, Selpia; G.S, Bambang; Rasyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCommon problem in this research is, internal factor especially on psychological aspect that is learning attitude, interest of learning, and motivation learn that influence student learning result on economy class XI IPS MAN 1 Pontianak